Problems of Population Banking of Commercial Banks - Gaibullaev Rakhim Murodovich; Isabekov Akmalbek Komolboevich (International Journal on Integrated Education, 2022)
This The article examines the methods of assessing the loan portfolio of commercial banks in Uzbekistan and the analysis of its criteria, as well as improving its methodology by classifying the bank loan portfolio by form and type, and thus explores the development of the lending system.